TPB Dalam Menciptakan Brand Awareness Guna Meningkatkan Purchase Intention - Difa Mutiara Sari; Yolanda Masnita; Annisa Ristya Nursaima (Value : Jurnal Manajemen dan Akuntansi, 2024)
Halal skincare products made from safe natural ingredients and certified halal are suitable for healthy skin care and in accordance with Islamic law. Previous research did not consider Brand Awareness in analyzing halal products. Using the Theory of Planned Behavior, the research findings indicate that Halal-Green Awareness influences consumer purchase intention, but Brand Awareness does not significantly affect halal-green awareness. This finding provides valuable insights for the halal beauty industry to develop more effective marketing strategies based on consumer trust in halal and environmentally friendly skincare products. This study can serve as a basis for further research on consumer preferences for halal skincare products in emerging markets. Recommendations for future research include expanding the scope of consumer characteristics, conducting comparative analyses between Muslim and non-Muslim consumers, and exploring the influence of other factors on purchase intention.